Off-season management with herbicides as an alternative to reduce weed infestation in paddy rice production systems - Guerra N. (2020)
© 2020, Sociedade Brasileira da Ciencia das Plantas Daninha. All rights reserved.Background: Weed management is a challenge in paddy rice production, mainly due to the dispersal of a population resistant to herbicides. Objective: To assess the efficacy of chemical weed control in the off-season to reduce weedy rice and other species in water-seeded or drilled rice. Methods: Two experiments were carried out in a flat field to water-seeded or drilled rice, in randomized block design. The water-seeded system treatments were organized in a split-plot design. In the plot were evaluated two water management in the off-season (with or without continuous flooding), and in the subplot nine herbicides-treatments were evaluated (Check, clomazone at 0.72 and 1.08 kg a.i. ha-1, oxadiazon at 1.00 and 1.50 kg a.i. ha-1, oxyfluorfen at 0.312 and 0.48 kg a.i. ha-1, S-metolachlor at 1.44 kg a.i. ha-1, and flumioxazin a 0.075 kg a.i. ha-1). In the drilled rice experiment, the treatments were organized in a two-factor factorial. The factor A was nine herbicides treatments (the same herbicide and rates applied in water-seeded experiment) and the factor B was two application time (73 and 43 days before of rice-sowing). Results: Off-season management was efficient to reduce weedy rice infestation only on the paddy rice system using the pre-germinated seeds. In this assay, flumioxazin was an efficient alternative to giant arrowhead control, however the selectivity of this herbicide treatment needs to be studied. In dry-seeded system, herbicide sprayed in off-season reduced barnyardgrass infestation until the paddy rice sowing. Conclusions: The off-season management was efficient to reduce weedy rice and giant arrowhead infestation in water-seeded system, and barnyardgrass infestation in drill-seeded system.